Edgar G. Ulmer : a filmmaker at the margins - Isenberg, Noah William (Weimar and now., 2013)
Edgar G. Ulmer is perhaps best known today for Detour, considered by many to be the epitome of a certain noir style that transcends its B-list origins. But in his lifetime he never achieved the celebrity of his fellow Austrian and German émigré directors-Billy Wilder, Otto Preminger, Fred Zinnemann, and Robert Siodmak. Despite early work with Max Reinhardt and F.W. Murnau, his auspicious debut with Siodmak on their celebrated Weimar classic People on Sunday, and the success of films like Detour and Ruthless, Ulmer spent most of his career as an itinerant filmmaker.